Tunable Q-switched fiber laser using zinc oxide nanoparticles as a saturable absorber - Ahmad, Harith; Lee, C.S.J.; Ismail, Mohd Afiq; Ali, Z.A.; Reduan, S.A.; Ruslan, N.E.; Harun, Sulaiman Wadi (Optical Society of America, 2016)
Nanomaterials have ignited new interest due to their distinctive electronic, mechanical, and optical properties. Zinc oxide nanostructures are fabricated into thin film and then inserted between two fiber ferrules to act as a saturable absorber (SA). The modulation depth and insertion loss of the SA are 5% and 3.5 dB, respectively. When the ZnO-SA is incorporated into the laser cavity, a stable Q-switched pulse tunable from 1536 to 1586 nm (50 nm range) with pulse energy up to 46 nJ was observed. Our result suggests that ZnO is a promising broadband SA to generate passively Q-switched fiber lasers.